Inherited social capital and residential mobility: A study using Japan panel data - Eiji Yamamuraa; Yoshiro Tsusuib; Chisako Yamanec; Shoko Yamaned (Osaka University, Institute of Social and Economic Research (ISER), 2014)
Empirical results based on individual-level data from Japan were studied to determine the effect of social capital on the willingness to leave one's residential area. It was found that social capital accumulated through one's own experience in a residential area is not the only factor that reduces willingness to leave. Social capital inherited from one's parents also negatively influences the desire to move.
Keywords: Z13; J61; 330; social capital; residential mobility